APPLICATION OF AUDIO LINGUAL LEARNING METHODS TO IMPROVE SPEAKING ABILITY - Lusiani Yuliarty; Johanes Sapri (UNIB Press, 2018)
This study aimed to describe the application of the Audio Linggual methods in improving speaking skill. This type of research, totaling 25 students. The research subject were 12th grade light vehicle engineering students totaling 25 students. Data collection techniques use test. The data analysis technique used is the average data of the students persiklus result and data analysis of t-test.. The result of study indicate that the application of the audio lingual method can improve speaking skills in English subject due to 12th grade of vocational school.